Smart solar powered system with integrated copper rod for electroculture of raphanus sativus - Aldenese, John Cristian V.; Palugod, Daynniel Arlo F.; Tagala, Ian Keanu D. 4 0 16; 5 (2024)
u
Undergraduate Thesis: (Bachelor of Science in Electrical Engineering) - Pamantasan ng Lungsod ng Maynila, 2024.
Keywords: 2 -- 0; 6; 20; 20; 2